Mobile signal cancellation device - Zabri @ Suhaimi, Siti Normi; Mohd Kasim, Noor Shahida; Yap, David Fook Weng (Universiti Teknikal Malaysia Melaka, 2011)
The number of users of mobile communication devices is rapidly increasing nowadays, proving the communications industry is very important. The use of mobile phones however generates electromagnetic radiation which then scatters to surrounding. The resulting radiation can generate problems and damages to human and surrounding. Sometimes, there is a growing demand for controlling the use of cellular phones in public places such as religious places, examination halls, libraries, and others. Therefore, it is important to block signal to and from mobile phone at certain areas. The overall aim of this project is to design and built a signal cancellation device for mobile phones. The device provides the advantage in preventing mobile phone from receiving and transmitting RF signal to base station.